PENDAMPINGAN SERTIFIKASI HALAL PADA UMKM C.DOFF COFFEE DI CIPUTAT, TANGERANG SELATAN - Alisa Sandrina Ramadhani (Media Resonansi Pengabdian Masyarakat, 2025)
C.Doff Coffee is a coffee processing MSME located in Ciputat, South Tangerang. All coffee drink products produced are based on cold brew or brewing coffee powder with cold water. The most popular coffee drink product is classic milk coffee. Apart from that, there are several other types of coffee drink products such as original coffee and palm sugar milk coffee. C.Doff Coffee wants to make the coffee products it produces halal certified, in addition to serving contemporary and healthy coffee. The halal certification process for MSME C.Doff Coffee includes socialization, document preparation, verification and validation, and approval. Halal certification aims to ensure that products are free from contamination from non-halal ingredients in accordance with Islamic law. In order for the C.Doff Coffee MSME halal certification application to meet the self-declare halal certification criteria, the advice that can be given to the company is for C.Doff Coffee MSMEs to change the KBLI type to meet the self-declare halal certification criteria, or register for the regular halal certification program.Keywords: halal certification, coffee drinks, self-declaration certification, micro small and medium enterprises